EVALUASI SISTEM DAN PROSEDUR PENGELUARAN KAS PADA DINAS KELAUTAN DAN PERIKANAN PROVINSI SULAWESI UTARA - Meilisa, Tumilaar Alvionita; Sondakh, Jullie J; Tinangon, Jantje J (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
Implement evaluation system and cash expenditure procedure of the most important components the resources for good government. Cash expenditure included transactions that resulted in a diminishing cash and or local bank accounts. The goal of research is to find out how effective the implementation systems and cash expenditure procedures at the Marine and Fisheries Office of Northern Sulawesi. The analysis method used is a descriptive analysis. Studies show that the implementation of cash expenditure systems and procedures for the Marine and Fisheries Office of the Northern SulawesiÂ  has been effective and according to SE 900/316/ BAKD includes related functions, documents used, generated reports and technical descriptions of the cash expenditure procedure. The should, head of Marine and Fisheries Office the Northern Sulawesi increase and maintain the effectiveness of system operations, cash expenditure and socializing as well as technical guidance to improve the quality of human resources and thus have a positive effect on implementation of the system and cash expenditure procedure.